KESADARAN HUKUM MASYARAKAT TERHADAP KEPEMILIKAN AKTA PERKAWINAN BERDASARKAN UNDANG-UNDANG NO. 1 TAHUN 1974 (STUDI PADA MASYARAKAT DI BANJAR PASTI) - Laksmi Danyathi, Ayu Putu (VYAVAHARA DUTA, 2018)
Indonesia as a State of Law, has some rules about marriage that is Law Number 1 Year 1974. Marriage is legitimate if it is  according to the laws  of their  each  religion  and  belief. Furthermore, there is also an obligation to register their marriage. Pasti is the name of a banjar that located in Pandak Gede Village, Kediri District, Tabanan Regency, Province of Bali. To prove that the marriage existed, Pasti’s citizens must have a Marriage Act. This  research  aims to  determine the level  of community legal  awareness in Banjar Pasti on marriage certificate ownership, and to know and examine the factors that affect it. This research uses empirical juridical approach method, that is using the existing factual approach by way of observation and research in the field, then studied and reviewed based on relevant legislation as a reference to solve the problem. Based on the research, it is found that the level of community legal awareness in Banjar Pasti on marriage certificate ownership based on Law Number 1 Year 1974 regarding Marriage is relatively high. This can be proved by the following indicators : (a). The high level of community law knowledge in Banjar Pasti on marriage certificate ownership. (b). The high level of community law  understanding in Banjar Pasti  on marriage certificate ownership.  (c). The  high level of community legal attitude in Banjar Pasti on marriage certificate ownership. (d). The high level of community legal behavior patterns in Banjar Pasti on marriage certificate ownership. The Factors influencing the  community legal  awareness in Banjar Pasti  on marriage  certificate ownership under Law Number 1 Year 1974 regarding Marriage, that is : Level of education, Age and Sex.